Explanation of the variable affecting of advertising Sales Phenomenon Using The Regression method (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The study examined the most important explanatory variables advertising and advertising as a means of attraction to consumers, which help to increase productivity and increase the quantity of sales by increasing the total demand for consumer goods subject to research (cosmetics industry), not one of the companies during the month to study this phenomenon was used one of the methods Statistical regression is the multiple linear regression and the use of one of the computer programs that contain statistical programs, includingSpssAnd through the indicators extracted that the explanatory variables have a significant impact on increasing the desire of consumers to buy this product and thus increase productivity to meet their desires, which reflected the increase in the amount of sales and representation by illustrations as they are more understanding of the reader in interpreting the results.